The influence of implementing classroom displays on student learning in mathematics - Flynn, K (2018)
Classroom displays are common place in primary school and even in secondary school however, there is little research to suggest the influence that classroom displays can have on students in further education settings such as a large mainstream college. This study aims to explore and contribute to this gap in literature regarding classroom displays for students aged 16+. Focusing on my own classroom practice, this study endeavours to assess the influence that introducing and implementing student-led classroom displays can have on student learning experiences such as motivation, confidence and mindset. This study attempts to answer the following research questions: • How has student motivation and confidence in the mathematics classroom changed with the implementation of displays? • How has student mindset changed with the implementation of displays? • Does giving students a voice in the creation of classroom displays promote or contribute to positive learning experiences? Questionnaires were completed before and after the implementation of the new classroom displays by 28 students and semi-structured interviews were also carried out with two students and one Education Support Worker. Findings suggest that implementing student-led and well planned displays can have a positive influence on student motivation, confidence and mindset. As a result of implementing new classroom displays, there was an overall shift of 89% from negative to positive opinions of maths. Furthermore, there was a 75% increase in students ‘liking’ or ‘loving’ maths. Significantly, pre intervention 11% of students thought the displays aided their learning compared to 96% post intervention, indicating a massive 85% change towards positive opinions.